Chemical and Sensory Properties of Spontaneous Fermented Red Rice Vinegar with Fermentation Time Variation - Pratiwi, Viera Nu’riza; Lidya Puspita Sumino Putri (Malaysian Journal of Science (MJS), 2025)
Red rice is a variety of Indonesian rice that contains anthocyanins, which are antioxidant compounds that can neutralize free radicals. Red rice is used as another valuable food source, specifically for vinegar. The fermentation duration determines the quality of vinegar in terms of chemical and sensory characteristics. The purpose of this study was to examine the effect of fermentation time on the chemical properties and sensory attributes of red rice vinegar made by spontaneous fermentation. Red rice vinegar was produced through a spontaneous fermentation process at 30- and 60-day fermentation periods. The pH, alcohol content, acetic acid, antioxidant activity, and total phenolic content were measured. Red rice vinegar produced after 30 and 60 days of fermentation had an acetic acid concentration of 73.02±4.91 mg GAE/G. The alcohol content differed significantly between 30 and 60 day fermentation treatments (p<0.05). The fermentation time has no effect on the sensory qualities (aroma, taste, and colour) of the product. The yeast aroma, slightly sweet, bitter flavour, and brownish yellow colour were the best treatments based on sensory evaluation.